2018
DOI: 10.1097/ta.0000000000001866
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital airway procedures performed in trauma patients by ground forces in Afghanistan

Abstract: Prognostic and epidemiological study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Supplementary Table S1 details the findings of each included study; the quality of evidence findings are available in Supplementary Table S2 . 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 56 , 57 , 58 , 59 , 60 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 Thirty-three studies were low quality and 36 were very low quality. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table S1 details the findings of each included study; the quality of evidence findings are available in Supplementary Table S2 . 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 56 , 57 , 58 , 59 , 60 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 Thirty-three studies were low quality and 36 were very low quality. …”
Section: Resultsmentioning
confidence: 99%
“…55 Particularly in the military studies, the training behind the medical team performing FONA is not always clear as they are referred to as ‘combat medics’ or ‘military medics’. 26 , 30 , 52 , 56 , 57 , 58 , 59 , 60 There are also differences worldwide in the setup of prehospital teams and the standard FONA technique used; the 2017 guidelines were based on the UK DAS guidelines and may therefore not have been utilised outside of the UK. 5 , 61 There is also difficulty in extracting success rates before and after 2017 in datasets that overlap this time period with different techniques still being used despite the update in guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Our model was based on factors that have been previously linked to poor outcomes (e.g. airway interventions) and the need for airway interventions as ketamine is frequently used as a sedative agent during rapid sequence intubation [16,17]. Significant variables were reported as odds ratios with 95% confidence intervals (OR, 95% CI).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Blackburn, et al reported that prehospital endotracheal intubation was performed in 68% of patients that received an airway intervention in the prehospital combat setting, with nearly 25% having a combat medic as the highest level of provider recorded in the patient record. 6 Clearing the airway is vital to airway management, as battlefield injuries can leave the airway clogged with blood, vomit, mucus, foreign bodies, and debris. 7 Airway suction, the act of using negative pressure in a patient's upper airway, removes debris that can prevent respiration, decreases possible aspiration risks, and allows clearer viewing of the airway for intubation.…”
Section: Introductionmentioning
confidence: 99%